INTEGRASI GROUP FACEBOOK KE DALAM COLLABTIVE SEBAGAI PERANGKAT LUNAK MANAJEMEN PROJEK MENGGUNAKAN FACEBOOK GRAPH API - , OLIVER JORDAN RAJAGUKGUK ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Project management software is collaborative software facilitating multiple users that are connected in a work environment and work together to accomplish tasks in a coordinated manner by using the available features of the software. Collabtive is web-based collaborative software that is open source providing the features to handle the project management activities. The purpose of this research is to develop Collabtive in terms of communication among users by integrating groups of Facebook inside. Facebook provides an API called Facebook Graph API that allows third party application development by utilizing the services of Facebook. Integration is done by using the Facebook Javascript SDK to handle the login and logout process, Facebook PHP SDK for data synchronization and posting process. By integrating with one of the well-known Facebook feature, that is group into Collabtive, is expected to provide a better means of communication among users, so that it can increase the strength of Collabtive as project management application. This research has resulted in a system that integrates group Facebook services into Collabtive. Authentication of users uses email and Facebook account passwords. The addition of user Collabtive is performed by selecting a group or Facebook friend. There is also a feature wall that displays determined Facebook group's wall. System is able to post texts, images, or links to the group. Then, it will be shown also in Collabtive. Moreover, it provides comments for each of the posts. Combination can be made to post text â images and text â links, but not for the images â links.